Output derivative feedback vibration control of an integrated vehicle suspension system - Yazici, Hakan; Sever, Mert (SAGE PUBLICATIONS LTD, 2020)
In this article, we present a novel approach to design an L-2 gain output derivative feedback controller for active vibration control of a vehicle suspension system. In vibration control problems, state derivative signals such as acceleration and velocity are easier to obtain rather than the state variables such as position and velocity, since the accelerometers are simpler, cheaper and more reliable than position sensors. First, an L-2 gain output derivative feedback controller is proposed by taking into account that measuring state derivative signals belong to driver body and electro-hydraulic actuator is not applicable in practice. Then, an L-2 gain state derivative feedback controller and an L-2 gain static output feedback controller are designed to investigate efficacy of the proposed controller. Performance of the controllers is tested against bump- and random-type road irregularities. A 4-degree-of-freedom integrated vehicle suspension model that includes a quarter vehicle suspension, a seat suspension, a driver body and an electro-hydraulic actuator is used throughout the numerical simulation studies. Simulation results show that proposed L-2 gain output derivative feedback controller provides compatible performance improvement in the state derivative feedback control and static output feedback control with more viable feedback strategy.
Keywords: Output derivative feedback; state derivative feedback; L-2 gain control; linear matrix inequalities; electro-hydraulic suspension system; H-INFINITY CONTROL; LMI-BASED DESIGNS; ACTIVE SUSPENSION; SEMIACTIVE SUSPENSIONS; MULTIOBJECTIVE CONTROL; SEAT SUSPENSION; POLE-PLACEMENT; MODEL; OPTIMIZATION; VELOCITY; Automation & Control Systems